2015
DOI: 10.1016/j.joen.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Administration of Parathyroid Hormone Ameliorates Periapical Lesions in Mice

Abstract: Introduction Intermittent administration of parathyroid hormone (PTH) promotes oral osseous wound healing and protects against ligature-induced alveolar bone loss. However, its therapeutic value on periapical periodontitis is unknown. The goal of this study was to determine the effect of intermittent PTH administration on the progression of periapical periodontitis. Methods Seven lymphotoxin alpha deficient mice received pulp exposures of mandibular first and second molars. Exposed pulp in the right mandible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Animals were randomly divided into the experimental (n = 30) and control group (n = 30). Rats in the experimental group received a daily subcutaneous injection of 40 µg/kg body weight PTH (1 to 34) dissolved in 0.1% acetic acid according to previous studies . In the control group, animals received the same volume of placebo vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were randomly divided into the experimental (n = 30) and control group (n = 30). Rats in the experimental group received a daily subcutaneous injection of 40 µg/kg body weight PTH (1 to 34) dissolved in 0.1% acetic acid according to previous studies . In the control group, animals received the same volume of placebo vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Anabolic treatments, such as teriparatide (human PTH (1-34), which effective against osteoporosis, may also help treat bone loss in both rat and mouse models of PD [33,34]. Interestingly, these previous studies reported antiresorptive and anti-in ammatory mechanisms for daily PTH injections instead of the well-known bone growth effects usually observed for PTH [33,34]. In one clinical trial, the application of PTH combined with periodontal surgery was superior to periodontal surgery alone at repairing localized bone defects [35].…”
Section: Discussionmentioning
confidence: 99%
“…Antiresorptive agents such as BPs are also known for their antiangiogenic actions that potentially are a risk factor for the development of osteonecrosis [33,34]. Anabolic treatments, such as teriparatide (human PTH , which effective against osteoporosis, may also help treat bone loss in both rat and mouse models of PD [35,36]. Interestingly, these previous studies reported antiresorptive and antiin ammatory mechanisms for daily PTH injections instead of the well-known bone growth effects usually observed for PTH [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Anabolic treatments, such as teriparatide (human PTH , which effective against osteoporosis, may also help treat bone loss in both rat and mouse models of PD [35,36]. Interestingly, these previous studies reported antiresorptive and antiin ammatory mechanisms for daily PTH injections instead of the well-known bone growth effects usually observed for PTH [35,36]. In one clinical trial, the application of PTH combined with periodontal surgery was superior to periodontal surgery alone at repairing localized bone defects [37].…”
Section: Discussionmentioning
confidence: 99%